Terra sigillata trade in Mesas do Castelinho (Almodôvar-Portugal): pattern of imports and contextual data in southern Lusitania - Viegas, Catarina (SPAL - Revista de Prehistoria y Arqueología, 2019)
Mesas do Castelinho (Almodôvar) is located in southern Portugal, an area traditionally recognized as a natural path connecting coastal region in the Algarve and the inland Alentejo region. Occuppied since 5th century BC, the site is still relevant during the Roman Republican phase. After the Augustan reforms it progressively loses importance to be abandoned at the end of the 1st century AD. Terra sigillata, recovered in the project directed by C. Fabião and A. Guerra is abundant and forms a set of 322 pieces. Main categories are Eastern sigillata A, Italian-type, South Gaulish, Hispanic (from Andújar and Tritium) and Peñaflor type sigillata (“sigillata de imitación tipo Peñaflor”), ARS A and Phocean red slip ware. Following the economic dynamics of the site, the major phase of imports took place in Augustan-Tiberian period with progressive decrease until the end of the urban settlement in late 1st century AD. Episodic presence in the end of the 5th century AD is testified by one fragment of Phocaean red slip ware. The strategic position of Mesas do Castelinho determined its role during the Islamic period with fortress and settlement from the 9th-10th until the12th century, affecting and disturbing previous Early Roman phases.